English skills - Langan, John (McGraw-Hill, 2006)
One of the most comprehensive and well-respected books of its kind, English skills, Eighth Edition, features John Langan's crystal-clear explanations and his wide range of motivating activities and writing assignments that reinforce the four essentials of good writing: unity, support, coherence and sentence skills. English skill continues to help students succeed with its focus on paragraph writing skills in preparation for essay writing. The eighth edition adds several new features.